Testosterone improves the differentiation efficiency of insulin-producing cells from human induced pluripotent stem cells - Liu, Haikun (PLoS One, 2017)
Human induced pluripotent stem cells (hiPSCs) may provide potential resource for regenerative medicine research, including generation of insulin-producing cells for diabetes research and insulin production. Testosterone (T) is an androgen hormone which promotes protein synthesis and improves the management of type 2 diabetes in clinical studies. Concurrently, co-existed hyperandrogenism and hyperinsulinism is frequently observed in polycystic ovary syndrome, congenital adrenal hyperplasia and some of Wermer's syndrome. However, the relationship among androgens, insulin and the differentiation of pancreatic β cells is still not fully clear. Here we find that T improves the differentiation efficiency of insulin-producing cells from hiPSCs. The addition of T into routine differentiation formula for pancreatic β cells increases the differentiation efficiency from 12% to 35%. The administration of T promotes the expression of key genes associated with β cells differentiation including NGN3, NEUROD1 and INS. This finding benefits the ongoing process to optimize the differentiation protocol of pancreatic β cells from hiPSCs, and provides some degree of understanding the clinical management of T for type 2 diabetes.